The Effectiveness of Collaborative Learning in The Teaching of Form Four Mathematical Reasoning. (Sains Humanika, 2011)
Collaborative learning refers to the form of classroom organization in which students work together, in small groups, on a shared activity and with a common goal. This study focused on looking at the effectiveness of collaborative learning in the teaching of form four mathematical reasoning, and the possible effects of gender on the instructional methods in a Malaysian government secondary school. This study also looked at the gender effects on interest toward learning mathematics and perceptions of the teaching methods. The study was carried out using a pretest-posttest quasi-experiment research design with one treatment group and one controlgroup. The study used two intact classes at a government secondary school in Kuching, Sarawak, Malaysia. The treatment class was taught using collaborative learning while the control class was taught using lecture-based instruction. The research instruments used in the study to collect data consisted of a pretest, posttest and questionnaire. The result showed that the collaborative learning group outperformed the traditional instructional group. In addition, female students obtained better results compared to male students in both of the instructional method. Majority of the students also preferred collaborative learning and collaborative learning group also showed higher interest in learning mathematics. However, the result showed that there were no gender effects on the instructional methods, interest toward learning mathematics and perceptions of the teaching methods.
Keywords: Collaborative; collaborative learning; effectiveness; gender; mathematical reasoning